Application of Juxtaposition Panel of Indonesian Comic - Yully Ambarsih Ekawardhani; D Subandi (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
The purpose of this research is to find the application of panel juxtaposition style in Indonesian comic entitled Jagabumi. Descriptive research method was used to get a description of the juxtaposition treatment on this heroic comic panel. The steps taken are in the form of a literature study on comics and local existence, as well as observations on the Jagabumi comic episode Kesatria. The result is an understanding of the displacement of objective reality and reality in the Jagabumi comics, especially the panels depicted in this episode. Juxtaposition in comics does not stop only at the comparison between two panels, but also the relationship between text and images. Episode Ksatria applies seven categories of juxtapositional style, which includes the creation of images with a local concept. This can be seen in the visual elements and written terms as expressions. By doing this research, it will reveal the renewal of reality through the panel juxtaposition style in the Jagabumi comic.